An uv-resistant weatherable pmma material
Patent Information
- Application Number
- CN202610957432.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]本发明的目的是提供一种抗UV耐候PMMA材料,以解决现有技术中PMMA材料抗紫外性能差、小分子紫外线吸收剂易迁移的技术问题
(1)本发明通过Knoevenagel缩合反应合成了含取代氰基丙烯酸酯(SCA)结构单元的2-氰基-3-苯基丙烯酸烯丙酯单体,其共轭体系能够有效吸收280~320 nm波段的UVB紫外线,赋予材料优异的紫外屏蔽性能。本发明通过自由基三元共聚将2-氰基-3-苯基丙烯酸烯丙酯、2-萘硫乙基丙烯酸酯(NTEA)与甲基丙烯酸甲酯共聚,使紫外吸收功能基团通过共价键永久性接入PMMA分子链中,从根本上避免了传统小分子紫外吸收剂在长期使用过程中的迁移、析出和挥发问题,赋予材料长效稳定的抗紫外耐候性能。
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials technology, specifically relating to a UV-resistant and weather-resistant PMMA material. Background Technology
[0002] Polymethyl methacrylate (PMMA), commonly known as plexiglass or acrylic, possesses excellent optical transparency, good processability, and surface gloss, making it widely used in architectural lighting, automotive parts, optical lenses, outdoor advertising, and electronic displays. However, the ester groups and tertiary carbon atoms in the PMMA molecular chain are highly sensitive to ultraviolet (UV) radiation. Under long-term outdoor exposure, UV radiation can trigger photo-oxidative degradation of the molecular chain, leading to gradual yellowing, decreased light transmittance, surface cracking, and even significant degradation of mechanical properties. This severely limits the lifespan and application range of PMMA in outdoor settings.
[0003] To address the aforementioned issues, existing technologies typically employ the method of adding small-molecule UV absorbers to PMMA. Commonly used UV absorbers include organic compounds such as benzophenones, benzotriazoles, and triazines. However, these small-molecule UV absorbers are dispersed in the PMMA matrix only through physical blending, and are prone to migration, precipitation, and volatilization during long-term use, leading to a gradual decline in UV protection. Furthermore, the precipitated additives may also affect the material's appearance and optical properties.
[0004] Therefore, there is an urgent need to develop a technical solution that can permanently introduce UV-absorbing functional groups into the PMMA molecular chain through covalent bonds while maintaining the material's excellent optical transparency, so as to fundamentally solve the problem of easy migration of small molecule UV absorbers and achieve long-term stable UV resistance and weather resistance. Summary of the Invention
[0005] The purpose of this invention is to provide a UV-resistant and weather-resistant PMMA material to solve the technical problems of poor UV resistance and easy migration of small molecule UV absorbers in existing PMMA materials.
[0006] The technical solution for achieving the objective of this invention is as follows.
[0007] In a first aspect, the present invention provides a UV-resistant and weather-resistant PMMA material, comprising the following components by weight: 60-95 parts of polymethyl methacrylate (PMMA), 5-40 parts of modified copolymer, and 0.5-5 parts of additives.
[0008] The additives include at least one of heat stabilizers, lubricants, and antioxidants.
[0009] The modified copolymer is a methyl methacrylate terpolymer containing substituted cyanoacrylate structural units and naphthioyl structural units, prepared by a method comprising the following steps: (1) Allyl cyanoacetate and benzaldehyde were condensed in the presence of an alkaline catalyst, and the product was washed, dried and purified by column chromatography to obtain 2-cyano-3-phenyl acrylate. The synthesis reaction formulas for the above process are as follows: .
[0010] Specifically, step (1) includes: adding allyl cyanoacetate and benzaldehyde in a molar ratio of 1:(1~1.2) to an organic solvent, stirring at room temperature until completely dissolved, adding an alkaline catalyst, heating the reaction system to 50~100℃, and stirring for 4~24 hours. The reaction process is monitored by TLC. After the reaction is complete, the mixture is cooled to room temperature, the solvent is removed by vacuum evaporation, dichloromethane is added to dissolve the crude product, and the product is washed successively with saturated sodium bicarbonate solution and saturated brine, and dried over anhydrous sodium sulfate. The solvent is removed by vacuum evaporation, and the crude product is purified by silica gel column chromatography (eluent: petroleum ether / ethyl acetate = 10:1~15:1). The target fraction is collected, and the eluent is removed by vacuum evaporation to obtain 2-cyano-3-phenylacrylate allyl ester. The alkaline catalyst is selected from at least one of piperidine, pyridine, ammonium acetate, potassium carbonate, and DMAP; the organic solvent is selected from at least one of anhydrous ethanol, methanol, tetrahydrofuran, and dimethylformamide.
[0011] (2) The 2-cyano-3-phenyl acrylate, 2-naphthyl thioethyl acrylate and methyl methacrylate were subjected to a free radical ternary copolymerization reaction in the presence of an initiator, and the modified copolymer was obtained by precipitation, filtration and drying.
[0012] Specifically, step (2) includes: adding 2-cyano-3-phenylacrylate, 2-naphthyl thioethyl acrylate, and methyl methacrylate to an organic solvent in a molar ratio of (0.005~0.1):(0.005~0.1):1, adding an initiator, and purging with nitrogen for 20~40 minutes to remove oxygen. The reaction system is heated to 60~100℃ and stirred under nitrogen protection for 4~12 hours. After the reaction is complete, the mixture is cooled to room temperature, and the reaction solution is slowly poured into a precipitant to precipitate. The precipitate is collected by filtration, washed 2~4 times with the precipitant, and dried in a vacuum drying oven to constant weight to obtain the modified copolymer. The initiator is at least one of azobisisobutyronitrile and benzoyl peroxide, and the amount of initiator is 0.1~2% of the total mass of the monomers; the organic solvent is selected from at least one of toluene, benzene, tetrahydrofuran, and dimethylformamide; the precipitant is selected from at least one of methanol, ethanol, and n-hexane.
[0013] Furthermore, the weight-average molecular weight of the modified copolymer is 10,000 to 200,000 g / mol.
[0014] In this invention, the 2-cyano-3-phenylacrylate and 2-naphthylthioethyl acrylate (NTEA) exhibit a significant synergistic effect in their UV protection function. Specifically: The cyanoacrylate structure in the 2-cyano-3-phenylacrylate molecule has a conjugated system (C=C-CN / COOR), with its maximum UV absorption wavelength around 303 nm, enabling efficient absorption of UVB ultraviolet radiation in the 280–320 nm band. The naphthalene ring in the NTEA molecule has an aromatic conjugated system, with its UV absorption mainly in the 290–350 nm band, effectively compensating for the insufficient absorption of 2-cyano-3-phenylacrylate in the UVA band (320–400 nm). The two complement each other in the UV absorption band—2-cyano-3-phenylacrylate primarily targets the UVB region, while the naphthalene ring of NTEA covers the UVA region and part of the UVB region—thus achieving broad-spectrum UV protection from UVB to UVA.
[0015] More importantly, the thioether bond (-S-) in the NTEA molecule endows the material with additional antioxidant properties. Under ultraviolet irradiation, the thioether group can be preferentially oxidized to sulfoxide or sulfone, consuming reactive oxygen species in the system, thereby protecting the conjugated structure of 2-cyano-3-phenylacrylate from oxidative damage and maintaining its ultraviolet absorption function for a long time. Simultaneously, the cyanoacrylate structure of 2-cyano-3-phenylacrylate can absorb ultraviolet light energy and convert it into heat energy through intramolecular isomerization, reducing the direct excitation of the thioether bond by light energy.
[0016] Through extensive experimentation, the inventors surprisingly discovered that the synergistic effect of 2-cyano-3-phenylacrylate allyl ester monomer and NTEA is not effective across all ratio ranges, but rather strongly depends on their molar ratio. When the molar ratio of 2-cyano-3-phenylacrylate allyl ester to NTEA is within a specific range of 1:0.5 to 1:0.8, an unexpected and significant synergistic effect is achieved, with the material's UV protection and antioxidant properties far exceeding the expected summation based on the individual contributions of each component.
[0017] Secondly, the present invention provides a method for preparing the UV-resistant and weather-resistant PMMA material as described above, comprising the following steps: By weight, 60-95 parts of polymethyl methacrylate, 5-40 parts of modified copolymer and 0.5-5 parts of additives are mixed evenly, and then melt-blended, extruded and granulated to obtain UV-resistant and weather-resistant PMMA material.
[0018] Furthermore, the melt blending temperature is 180~250℃ and the time is 5~20 minutes; the extrusion is carried out using a twin-screw extruder with a screw speed of 100~300 rpm.
[0019] Thirdly, the present invention provides the application of the UV-resistant and weather-resistant PMMA material as described above in outdoor building materials, automotive parts, optical lenses, outdoor advertising products, and electronic display devices.
[0020] By adopting the above technical solution, the present invention has the following beneficial effects: (1) This invention synthesizes 2-cyano-3-phenylacrylate allyl ester monomer containing substituted cyanoacrylate (SCA) structural units via Knoevenagel condensation reaction. Its conjugated system can effectively absorb UVB ultraviolet rays in the 280~320 nm band, giving the material excellent UV shielding performance. This invention copolymerizes 2-cyano-3-phenylacrylate allyl ester, 2-naphthylthioethyl acrylate (NTEA) and methyl methacrylate via free radical ternary copolymerization, so that the UV-absorbing functional groups are permanently incorporated into the PMMA molecular chain through covalent bonds. This fundamentally avoids the migration, precipitation and volatilization problems of traditional small molecule UV absorbers during long-term use, and gives the material long-term stable UV resistance and weather resistance.
[0021] (2) The NTEA introduced in this invention has multiple synergistic functions: the naphthalene ring conjugated system can absorb UVA ultraviolet rays, forming a band complement with the UVB absorption of 2-cyano-3-phenylacrylate, thus achieving broad-spectrum ultraviolet protection; the thioether bond (-S-) can be preferentially oxidized to sulfoxide or sulfone, consuming reactive oxygen species, protecting the conjugated structure of 2-cyano-3-phenylacrylate from being destroyed, and forming a synergistic antioxidant effect with the 2-cyano-3-phenylacrylate group. Through a large number of experiments, it was found that within a specific range of 1:0.5 to 1:0.8 molar ratio of 2-cyano-3-phenylacrylate to NTEA, the light energy conversion of 2-cyano-3-phenylacrylate and the reactive oxygen capture of NTEA thioether form an optimal synergistic cycle, achieving unexpected technical effects in anti-ultraviolet aging and antioxidant performance.
[0022] (3) The preparation process of this invention is simple, and it is compatible with existing PMMA processing equipment, making it suitable for large-scale industrial production. Detailed Implementation
[0023] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.
[0024] In the following examples, allyl cyanoacetate (purity ≥98%, CAS No.: 13361-32-5) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; benzaldehyde (purity ≥99%) was purchased from Sinopharm Chemical Reagent Co., Ltd.; 2-naphthylthioethyl acrylate (NTEA, purity ≥98%, CAS No.: 897049-32-0) was purchased from Zhejiang Yangfan New Material Co., Ltd.; methyl methacrylate (purity ≥99%, containing polymerization inhibitor) was purchased from Shanghai Maclean Biochemical Technology Co., Ltd., and the polymerization inhibitor was removed by vacuum distillation before use; azobisisobutyronitrile (AIBN, purity ≥98%) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; PMMA resin (injection molding grade) was purchased from Zhenjiang Chimei Chemical Co., Ltd.; and all other reagents were of analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.
[0025] Example 1
[0026] This embodiment provides a UV-resistant and weather-resistant PMMA material and its preparation method.
[0027] (I) Preparation of modified copolymers (1-1) Preparation of 2-cyano-3-phenylacrylate (SCA monomer): 1.25 g (10 mmol) of allyl cyanoacetate and 1.06 g (10 mmol) of benzaldehyde were added to a round-bottom flask containing 20 mL of anhydrous ethanol and stirred at room temperature until completely dissolved. 0.15 g of piperidine was added as a catalyst, and the reaction mixture was heated to 78 °C and refluxed, stirred for 8 hours. The reaction progress was monitored by TLC (eluent: petroleum ether / ethyl acetate = 10:1). After the reaction was complete, the mixture was cooled to room temperature, and the ethanol was removed by evaporation under reduced pressure. The crude product was dissolved in 50 mL of dichloromethane and washed successively with saturated sodium bicarbonate solution (20 mL × 2 times) and saturated brine (20 mL × 2 times), and dried over anhydrous sodium sulfate. The solvent was removed by evaporation under reduced pressure, and the crude product was purified by silica gel column chromatography (eluent: petroleum ether / ethyl acetate = 15:1, R_f = 0.40) to give 1.85 g of 2-cyano-3-phenylacrylate (pale yellow liquid), yield 86%.
[0028] (1-2) Preparation of modified copolymers (SCA / NTEA / MMA ternary copolymer, SCA:NTEA≈1:0.65): 9.40 g (94 mmol) of methyl methacrylate, 0.20 g (0.93 mmol) of 2-cyano-3-phenylacrylate, 0.16 g (0.60 mmol) of 2-naphthyl thioethyl acrylate (SCA:NTEA molar ratio ≈ 1:0.65) and 0.02 g of AIBN were added to a three-necked flask containing 50 mL of toluene, and nitrogen gas was purged for 30 minutes to remove oxygen. The reaction system was heated to 70 °C and stirred for 6 hours under nitrogen protection. After the reaction was completed, the mixture was cooled to room temperature, and the reaction solution was slowly poured into 200 mL of methanol to precipitate. The precipitate was collected by filtration, washed three times with methanol, and dried to constant weight in a vacuum drying oven at 50 °C to obtain 8.1 g of modified copolymer (white powder), with a yield of 81%. GPC (THF, PS standard): M_n = 43,000 g / mol, M_w / M_n = 1.9.
[0029] (II) Preparation of UV-resistant and weather-resistant PMMA materials By weight, 80 parts PMMA resin, 20 parts modified copolymer, 0.3 parts antioxidant 1010, and 0.2 parts lubricant stearic acid were added to a high-speed mixer and stirred at 500 rpm for 10 minutes to obtain a premix. The premix was then melt-extruded in a twin-screw extruder. The extruder temperatures were set as follows: Zone 1 180℃, Zone 2 200℃, Zone 3 210℃, Zone 4 215℃, and Zone 5 210℃, with a screw speed of 200 rpm. The extrudate was water-cooled and granulated to obtain a UV-resistant and weather-resistant PMMA material.
[0030] Example 2
[0031] The difference between this embodiment and Embodiment 1 is that the molar ratio of SCA:NTEA is different (SCA:NTEA≈1:0.5).
[0032] (1-1) Preparation of 2-cyano-3-phenylacrylate: Same as in Example 1.
[0033] (1-2) Preparation of modified copolymers (SCA / NTEA / MMA ternary copolymer, SCA:NTEA≈1:0.5): 9.42 g (94.2 mmol) of methyl methacrylate, 0.20 g (0.93 mmol) of 2-cyano-3-phenylacrylate, 0.12 g (0.47 mmol) of 2-naphthyl thioethyl acrylate (SCA:NTEA molar ratio ≈ 1:0.5) and 0.02 g of AIBN were added to a three-necked flask containing 50 mL of toluene, and nitrogen gas was purged for 30 minutes to remove oxygen. The reaction system was heated to 70 °C and stirred for 6 hours under nitrogen protection. After the reaction was completed, the mixture was cooled to room temperature, and the reaction solution was slowly poured into 200 mL of methanol to precipitate. The precipitate was collected by filtration, washed three times with methanol, and dried to constant weight in a vacuum drying oven at 50 °C to obtain 8.2 g of modified copolymer (white powder), with a yield of 82%.
[0034] The preparation steps for the UV-resistant and weather-resistant PMMA material are the same as in Example 1.
[0035] Example 3
[0036] The difference between this embodiment and Embodiment 1 is that the molar ratio of SCA:NTEA is different (SCA:NTEA≈1:0.8).
[0037] (1-1) Preparation of 2-cyano-3-phenylacrylate: Same as in Example 1.
[0038] (1-2) Preparation of modified copolymers (SCA / NTEA / MMA ternary copolymer, SCA:NTEA≈1:0.8): 9.38 g (93.8 mmol) of methyl methacrylate, 0.20 g (0.93 mmol) of 2-cyano-3-phenylacrylate, 0.19 g (0.74 mmol) of 2-naphthyl thioethyl acrylate (SCA:NTEA molar ratio ≈ 1:0.8) and 0.02 g of AIBN were added to a three-necked flask containing 50 mL of toluene, and nitrogen gas was purged for 30 minutes to remove oxygen. The reaction system was heated to 70 °C and stirred for 6 hours under nitrogen protection. After the reaction was completed, the mixture was cooled to room temperature, and the reaction solution was slowly poured into 200 mL of methanol to precipitate. The precipitate was collected by filtration, washed three times with methanol, and dried to constant weight in a vacuum drying oven at 50 °C to obtain 7.9 g of modified copolymer (white powder), with a yield of 79%.
[0039] The preparation steps for the UV-resistant and weather-resistant PMMA material are the same as in Example 1.
[0040] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no modified copolymer was added, and only pure PMMA resin was used.
[0041] By weight, 100 parts PMMA resin, 0.3 parts antioxidant 1010, and 0.2 parts lubricant stearic acid were added to a high-speed mixer and stirred at 500 rpm for 10 minutes to obtain a premix. The premix was then melt-extruded in a twin-screw extruder. The extruder temperatures were set as follows: Zone 1 180℃, Zone 2 200℃, Zone 3 210℃, Zone 4 215℃, and Zone 5 210℃, with a screw speed of 200 rpm. The extrudate was water-cooled and granulated to obtain PMMA material.
[0042] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the modified copolymer is replaced with a small molecule ultraviolet absorber UV3030 (cyanoacrylate).
[0043] By weight, 80 parts PMMA resin, 0.5 parts UV3030 (equivalent to the molar amount of UV-absorbing functional groups contained in the modified copolymer in Example 1), 0.3 parts antioxidant 1010, and 0.2 parts lubricant stearic acid were added to a high-speed mixer and stirred at 500 rpm for 10 minutes to obtain a premix. The premix was then melt-blended and extruded in a twin-screw extruder. The temperatures of each section of the extruder were set as follows: Zone 1 180°C, Zone 2 200°C, Zone 3 210°C, Zone 4 215°C, and Zone 5 210°C, with a screw speed of 200 rpm. The extrudate was water-cooled and granulated to obtain PMMA material.
[0044] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that 2-naphthyl thioethyl acrylate (i.e., SCA / MMA binary copolymer) is not added in the preparation of the modified copolymer.
[0045] (1-1) Preparation of 2-cyano-3-phenylacrylate: Same as in Example 1.
[0046] (1-2) Preparation of modified copolymers (SCA / MMA binary copolymer): 9.6 g (96 mmol) of methyl methacrylate, 0.20 g (0.93 mmol) of 2-cyano-3-phenylacrylate and 0.02 g of AIBN were added to a three-necked flask containing 50 mL of toluene, and nitrogen gas was bubbled through the flask for 30 minutes to remove oxygen. The reaction system was heated to 70 °C and stirred under nitrogen protection for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, and the reaction solution was slowly poured into 200 mL of methanol to precipitate the product. The precipitate was collected by filtration, washed three times with methanol, and dried in a vacuum drying oven at 50 °C to constant weight, yielding 8.2 g of the modified copolymer (SCA / MMA binary copolymer), with a yield of 82%.
[0047] The preparation steps for the UV-resistant and weather-resistant PMMA material are the same as in Example 1.
[0048] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that 2-cyano-3-phenylacrylate (i.e., NTEA / MMA binary copolymer) is not added in the preparation of the modified copolymer.
[0049] (1-1) Preparation of modified copolymer (NTEA / MMA binary copolymer): 9.6 g (96 mmol) of methyl methacrylate, 0.16 g (0.60 mmol) of 2-naphthyl thioethyl acrylate, and 0.02 g of AIBN were added to a three-necked flask containing 50 mL of toluene, and nitrogen gas was bubbled through the flask for 30 minutes to remove oxygen. The reaction mixture was heated to 70 °C and stirred under nitrogen protection for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, and the reaction solution was slowly poured into 200 mL of methanol to precipitate the product. The precipitate was collected by filtration, washed three times with methanol, and dried in a vacuum drying oven at 50 °C to constant weight, yielding 8.3 g of the modified copolymer (NTEA / MMA binary copolymer), with a yield of 83%.
[0050] The preparation steps for the UV-resistant and weather-resistant PMMA material are the same as in Example 1.
[0051] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the molar ratio of SCA:NTEA is approximately 1:0.3.
[0052] (1-1) Preparation of 2-cyano-3-phenylacrylate: Same as in Example 1.
[0053] (1-2) Preparation of modified copolymers (SCA / NTEA / MMA ternary copolymer, SCA:NTEA≈1:0.3): 9.45 g (94.5 mmol) of methyl methacrylate, 0.20 g (0.93 mmol) of 2-cyano-3-phenylacrylate, 0.072 g (0.28 mmol) of 2-naphthyl thioethyl acrylate (SCA:NTEA molar ratio ≈ 1:0.3) and 0.02 g of AIBN were added to a three-necked flask containing 50 mL of toluene, and nitrogen gas was purged for 30 minutes to remove oxygen. The reaction system was heated to 70 °C and stirred under nitrogen protection for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, and the reaction solution was slowly poured into 200 mL of methanol to precipitate. The precipitate was collected by filtration, washed three times with methanol, and dried in a vacuum drying oven at 50 °C to constant weight, yielding 8.3 g of modified copolymer (white powder), with a yield of 83%.
[0054] The preparation steps for the UV-resistant and weather-resistant PMMA material are the same as in Example 1.
[0055] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the molar ratio of SCA:NTEA is approximately 1:1.2.
[0056] (1-1) Preparation of 2-cyano-3-phenylacrylate: Same as in Example 1.
[0057] (1-2) Preparation of modified copolymers (SCA / NTEA / MMA ternary copolymer, SCA:NTEA≈1:1.2): 9.30 g (93 mmol) of methyl methacrylate, 0.20 g (0.93 mmol) of 2-cyano-3-phenylacrylate, 0.29 g (1.12 mmol) of 2-naphthyl thioethyl acrylate (SCA:NTEA molar ratio ≈ 1:1.2) and 0.02 g of AIBN were added to a three-necked flask containing 50 mL of toluene, and nitrogen gas was purged for 30 minutes to remove oxygen. The reaction system was heated to 70 °C and stirred under nitrogen protection for 6 hours. After the reaction was completed, the mixture was cooled to room temperature, and the reaction solution was slowly poured into 200 mL of methanol to precipitate. The precipitate was collected by filtration, washed three times with methanol, and dried in a vacuum drying oven at 50 °C to constant weight, yielding 7.6 g of modified copolymer (white powder), with a yield of 76%.
[0058] The preparation steps for the UV-resistant and weather-resistant PMMA material are the same as in Example 1.
[0059] Performance testing The PMMA materials prepared in the examples and comparative examples were subjected to the following performance tests: (1) Ultraviolet protection performance: According to GB / T 18830-2009, the ultraviolet transmittance of the plate at 303 nm and 330 nm was tested using an ultraviolet-visible spectrophotometer.
[0060] (2) Ultraviolet absorber migration test: The plate was placed in an 80℃ oven for accelerated aging for 7 days, and the change in ultraviolet light transmittance at 303 nm before and after aging was tested.
[0061] (3) Weather resistance: Ultraviolet accelerated aging test was conducted according to GB / T 16422.3-2014 (UVA-340 lamp, 0.76 W / m). 2 The test was conducted at 60℃ for 8 hours and 50℃ for 4 hours, with a total time of 1000 hours, to measure the change in the yellow index (YI) before and after aging.
[0062] (4) Optical performance: transmittance and haze were tested according to GB / T 2410-2008.
[0063] (5) Antioxidant performance: The scavenging rate of the board against ABTS free radicals was tested according to the ABTS free radical scavenging method.
[0064] The test results are shown in Table 1.
[0065] Table 1 Performance test results of the examples and comparative examples
[0066] The test results in Table 1 show that: (1) The transmittance of 303 nm ultraviolet light in Examples 1 to 3 was less than 6.5%, and the transmittance of 330 nm was less than 36%, with a ΔYI value ≤ 1.7, which was significantly better than Comparative Example 1 (pure PMMA, ΔYI=18.1) and Comparative Example 2 (small molecule UV3030, transmittance change rate after aging +217.2%). This shows that the dual ultraviolet absorption structure of SCA and NTEA introduced by the present invention through copolymerization can effectively absorb ultraviolet light, and the migration problem of small molecule ultraviolet absorbers is avoided by covalent bond anchoring, thus achieving long-term stable anti-ultraviolet weather resistance.
[0067] (2) Comparison of Comparative Example 3 (SCA only, 330 nm transmittance 52.3%, ABTS scavenging rate 38.2%) and Comparative Example 4 (NTEA only, 303 nm transmittance 42.5%) with Examples 1-3 shows that: after SCA and NTEA are used together, the UV transmittance at 303 nm and 330 nm is significantly lower than the sum of the expected values when used alone, and the ABTS scavenging rate is significantly improved, proving that the two have a significant synergistic effect in UV absorption and anti-oxidation.
[0068] (3) The 330 nm transmittance (42.8%) and ABTS scavenging rate (48.5%) of Comparative Example 5 (SCA:NTEA=1:0.3, below the lower limit of the range) were significantly worse than those of Example 2 (1:0.5), and ΔYI (3.5) was also significantly higher than that of Example 2 (1.7), indicating that an effective synergistic effect could not be formed when the NTEA content was too low.
[0069] (4) Comparative Example 6 (SCA:NTEA = 1:1.2, higher than the upper limit of the range) has good UV protection (303nm transmittance 5.2%, ΔYI = 1.8), but the transmittance drops to 89.5%, the haze rises sharply to 2.1%, and the optical transparency is severely degraded, failing to meet the basic requirement of high transparency for PMMA materials. This proves the scientific rationality and necessity of setting the upper limit of the SCA:NTEA ratio to 1:0.8 in this invention.
[0070] (5) The transmittance of Examples 1 to 3 all reached over 91%, and the haze was less than 1.0%, indicating that the introduction of the modified copolymer had little effect on the optical transparency of PMMA and was suitable for application scenarios with high optical performance requirements.
[0071] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A UV-resistant and weather-resistant PMMA material, characterized in that, By weight, it includes the following components: 60-95 parts polymethyl methacrylate, 5-40 parts modified copolymer, and 0.5-5 parts additives; The modified copolymer is composed of The method includes the following steps to prepare: (1) Allyl cyanoacetate and benzaldehyde were condensed in the presence of an alkaline catalyst, and the product was washed, dried and purified by column chromatography to obtain 2-cyano-3-phenyl acrylate. (2) The 2-cyano-3-phenyl acrylate, 2-naphthyl thioethyl acrylate and methyl methacrylate were subjected to a free radical ternary copolymerization reaction in the presence of an initiator, and the modified copolymer was obtained by precipitation, filtration and drying. In step (2), the molar ratio of 2-cyano-3-phenyl acrylate to 2-naphthyl thioethyl acrylate is 1:0.5 to 1:0.
8.
2. The UV-resistant and weather-resistant PMMA material according to claim 1, characterized in that, The molar ratio of allyl cyanoacetate to benzaldehyde in step (1) is 1:(1~1.2); the alkaline catalyst is selected from at least one of piperidine, pyridine, ammonium acetate, potassium carbonate, and DMAP.
3. The UV-resistant and weather-resistant PMMA material according to claim 1, characterized in that, In step (2), the molar ratio of 2-cyano-3-phenylacrylate, 2-naphthyl thioethyl acrylate and methyl methacrylate is (0.005~0.1):(0.005~0.1):1; the initiator is at least one of azobisisobutyronitrile and benzoyl peroxide, and the amount of initiator is 0.1~2% of the total mass of monomers.
4. The UV-resistant and weather-resistant PMMA material according to claim 1, characterized in that, The modified copolymer has a weight-average molecular weight of 10,000 to 200,000 g / mol.
5. The UV-resistant and weather-resistant PMMA material according to claim 1, characterized in that, The additives include at least one of heat stabilizers, lubricants, and antioxidants.
6. A method for preparing a UV-resistant and weather-resistant PMMA material as described in any one of claims 1 to 5, characterized in that, Includes the following steps: By weight, 60-95 parts of polymethyl methacrylate, 5-40 parts of modified copolymer and 0.5-5 parts of additives are mixed evenly, and then melt-blended, extruded and granulated to obtain UV-resistant and weather-resistant PMMA material.
7. The preparation method according to claim 6, characterized in that, The melt blending temperature is 180~250℃ and the time is 5~20 minutes; the extrusion is carried out using a twin-screw extruder with a screw speed of 100~300 rpm.